2015
DOI: 10.1038/mi.2014.81
|View full text |Cite
|
Sign up to set email alerts
|

MAIT cells are licensed through granzyme exchange to kill bacterially sensitized targets

Abstract: Mucosal-associated invariant T (MAIT) cells are an innate-like T-cell population restricted by the non-polymorphic, major histocompatibility complex class I-related protein 1, MR1. MAIT cells are activated by a broad range of bacteria through detection of riboflavin metabolites bound by MR1, but their direct cytolytic capacity upon recognition of cognate target cells remains unclear. We show that resting human MAIT cells are uniquely characterized by a lack of granzyme (Gr) B and low perforin expression, key g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
418
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(443 citation statements)
references
References 56 publications
22
418
2
1
Order By: Relevance
“…As 10% of CD8 + T cell express MAIT cell markers (Cosgrove et al 2013;Dusseaux et al 2011;Fergusson et al 2016;Walker et al 2012), similar to observations from the current study, this indicates that CD8 + Vα7.2 + CD161 + MAIT cells are a substantial population with particular relevance given the preferential mobilization of CD8 + cells following exercise (Campbell et al 2008;Gannon et al 2001;Simpson et al 2008). While CTLs and MAIT cells share similar cytotoxicity mechanisms (Kurioka et al 2015), the traditional targets of these respective cells are viral and bacterial infections (Dusseaux et al 2011;Gold et al 2010), although recent evidence argues otherwise . However, failing to exclude MAIT cells when assessing classic CTL function likely underestimates normalized cytotoxic function.…”
Section: Discussionsupporting
confidence: 76%
“…As 10% of CD8 + T cell express MAIT cell markers (Cosgrove et al 2013;Dusseaux et al 2011;Fergusson et al 2016;Walker et al 2012), similar to observations from the current study, this indicates that CD8 + Vα7.2 + CD161 + MAIT cells are a substantial population with particular relevance given the preferential mobilization of CD8 + cells following exercise (Campbell et al 2008;Gannon et al 2001;Simpson et al 2008). While CTLs and MAIT cells share similar cytotoxicity mechanisms (Kurioka et al 2015), the traditional targets of these respective cells are viral and bacterial infections (Dusseaux et al 2011;Gold et al 2010), although recent evidence argues otherwise . However, failing to exclude MAIT cells when assessing classic CTL function likely underestimates normalized cytotoxic function.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, CD56 bright NK cells are known for their proliferative capacity in response to cytokines;88 for example, liver‐resident CD49a+ NK cells have been found to express high levels of CD25, and were able to proliferate in response to low doses of IL‐2 89. CD161++ CD8+ T‐cells are also highly proliferative upon stimulation with IL‐12 and IL‐15 compared with the CD161+ CD8+ T‐cell counterparts 90, 91…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 99%
“…Resting CD161++ CD8+ T‐cells, in particular the MAIT cells, express no GrB and little perforin, and instead are uniquely enriched for GrK expression 90. In turn, CD161+ CD8+ T‐cells are enriched for GrB and perforin expression, even compared with their CD161− CD8+ T‐cell counterparts 16.…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria lacking the vitamin B2 (riboflavin) synthesis pathway are unable to activate MAIT cells through their specific TCR [9][10][11][12]. IL-12 and IL-18 cytokines can also activate MAIT cells in a TCR-independent manner since these innate-like T cells express high level of 7,13,14]. Recent studies have reported a critical role of MAIT cells in mucosal immune defense during bacterial infections [15].…”
mentioning
confidence: 99%